Time for genome editing: next-generation attenuated Malaria parasites - Singer, Mirko; Frischknecht, Friedrich (Trends in parasitology, 2017)
Immunization with malaria parasites that developmentally arrest in or immediately after the liver stage is the only way currently known to confer sterilizing immunity in both humans and rodent models. There are various ways to attenuate parasite development resulting in different timings of arrest, which has a significant impact on vaccination efficiency. To understand what most impacts vaccination efficiency, newly developed gain-of-function methods can now be used to generate a wide array of differently attenuated parasites. The combination of multiple attenuation approaches offers the potential to engineer efficiently attenuated Plasmodium parasites and learn about their fascinating biology at the same time. Here we discuss recent studies and the potential of targeted parasite manipulation using genome editing to develop live attenuated malaria vaccines.